Diversity and Vertical Distribution of Epiphytic Angiosperms, in Natural and Disturbed Forest on the Northern Coast of Jalisco, Mexico - Flores-Argüelles, Alejandra; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Krömer, Thorsten (Frontiers in Forests and Global Change, 2022)
Epiphytes are an important component of tropical forests, also they are sensitive to disturbance, since they depend on their host trees. The aim of this study was to analyze the differences in species richness, composition, and vertical distribution of epiphytic angiosperms between areas with natural and disturbed forest at the Northern Coast of Jalisco state, Mexico. The presence/absence was evaluated in each vertical zone of a selected tree, as well as those present in the understory, both in natural and disturbed sites in three types of vegetation (gallery forest, oak forest, tropical semideciduous forest) with a total of 30 plots of 20 x 20 m. Alpha diversity was calculated, as well as species beta diversity between habitats. An analysis of variance was performed to determine if there was a significant difference in species richness between sites and, also to compare the height and diameter at breast height (DBH) of the host trees. Multivariate analyzes were used to group the sites according to their floristic composition. Furthermore, a linear regression was performed to detect any relationship between the number of species and the phorophyte structure. We recorded 45 species, 29 genera and nine families of epiphytic angiosperms. The most diverse families were Bromeliaceae and Orchidaceae and the richest genus was Tillandsia. A significant difference in richness was not found, except for the disturbed gallery forest. Epiphytic angiosperms presented a high beta diversity, sharing only between 2 and 18 % of the recorded species. The inner portion of the canopy (Z3 and Z4) hosted most of the species and the understory had a high representation of epiphytes except for the disturbed oak forest, where these were absent. A relationship between the DBH and the number of species was found only at the disturbed sites. The diversity of epiphytic angiosperm species has not been severely affected by the human disturbance. Most of the species have morphological and physiological adaptations that allow their establishment and survival in adverse climatic conditions. Our results suggest that for epiphytic angiosperms, species composition seems to be a better indicator for the effect of disturbance than species richness.